Dukungan Sosial dalam Melakukan Vasektomi di Kecamatan Tanggulangin Kabupaten Sidoarjo - Dwi Ayu Cahyani (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2017)
According to BKKBN, men are still minimal to want to do a vasectomy because they think there are many other contraceptives, lack of knowledge about vasectomy, and also the myths circulating in the community about vasectomy. Sidoarjo regency growth rate according to BPS East Java in 2015 was 1.60%, growth rate of Sidoarjo regency was the highest in East Java compared to other districts. Tanggulangin sub-district was the second lowest districts of active male KB participants from 18 districts in Sidoarjo District. The purpose of this study was to analyze social support that affect the participation of men in doing Vasectomy in Tanggulangin sub-district, Sidoarjo Regency. The kind of research used was observational with descriptive research method, because that was done to identify influencing behavior factors of man  whom lack participation in family planning. The research design that used was cross sectional because just describes the relationship between social support factors with men doing vasectomy. Respondents were taken from the population using purposive sampling 50 people in total. The conclusion of this study is the level of social support by respondents who do not do vasectomy concluded enough with the details of respondents who have low social support as much as 16%, who have enough social support as much as 70% and who have high social support as much as 14% . Based on the result of the research, it was suggested to conduct routine socialization and service activities, provide assistance to KB cadres and PLKB and provide information and education about male KB to wife and also mass media.